2019
DOI: 10.1111/1346-8138.15149
|View full text |Cite
|
Sign up to set email alerts
|

Topical administration of nanocarrier miRNA‐210 antisense ameliorates imiquimod‐induced psoriasis‐like dermatitis in mice

Abstract: Psoriasis is a chronic, recurrent inflammatory autoimmune skin disease. Although its etiology and pathogenesis are complex and multifarious, it has been proved to be closely related to dysregulation of immune cell function as well as keratinocyte proliferation/differentiation. Our previous study demonstrated that miRNA-210 (miR-210) plays an important role in the formation of skin lesions and immune imbalance in psoriasis. Here, we developed a biomimetic reconstituted high-density lipoprotein (rHDL) nanocarrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Intriguingly, a recent study developed nanocarrier gel containing miR-210 antisense (NG-anti-miR-210) to topically inhibit miR-210 expression in the imiquimod-induced mouse model of psoriasis. The results showed that inhibition of miR-210 significantly alleviates psoriasis-like inflammation in mice with a decreased proportion of Th1 and Th17 cells in dermal and splenic cells, which paves the way for RNA drug development for psoriasis (67). miR-138 is significantly downregulated in CD4 + T cells from psoriasis patients (11,55).…”
Section: Mirnas Work In Concert To Distort Cd4 + T Cell Subsets Balancementioning
confidence: 91%
“…Intriguingly, a recent study developed nanocarrier gel containing miR-210 antisense (NG-anti-miR-210) to topically inhibit miR-210 expression in the imiquimod-induced mouse model of psoriasis. The results showed that inhibition of miR-210 significantly alleviates psoriasis-like inflammation in mice with a decreased proportion of Th1 and Th17 cells in dermal and splenic cells, which paves the way for RNA drug development for psoriasis (67). miR-138 is significantly downregulated in CD4 + T cells from psoriasis patients (11,55).…”
Section: Mirnas Work In Concert To Distort Cd4 + T Cell Subsets Balancementioning
confidence: 91%
“…The expression of miR‐210 was enhanced by TGF‐β and IL‐23 by inducing HIF‐1α responsible for histone H3 acetylation in the miR‐210 promoter region. This study suggested that inhibition of miR‐210 effectively reduces psoriasis‐like inflammation and can be a potential therapeutic approach 18,19 …”
Section: Mirna In Psoriasismentioning
confidence: 86%
“…In addition, there was improved erythema, scales, acanthosis, and dermal inflammatory cell infiltration. There was a decrease in interleukin‐17A, c‐interferon mRNA levels, and proportion of T‐helper 1 (Th‐1) and Th‐17 cells in dermal and splenic cells 18 . The miR‐210 found to inhibit Th2 differentiation by suppressing STAT6 and LYN expression leading to an immune imbalance in psoriasis development.…”
Section: Mirna In Psoriasismentioning
confidence: 99%
“…After Feng et al (28) demonstrated in a previous study the involvement of microRNAs (miRNAs/miRs) in the pathogenesis of psoriasis, an anti-psoriasis effect was obtained after topical administration of antisense miRNA-210 in a reconstituted high-density lipoprotein nano-transporter gel.…”
Section: Summary and Discussion Of The New Topical Treatment Strategiesmentioning
confidence: 99%